2019
DOI: 10.3892/etm.2019.7155
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of dexmedetomidine in reducing post‑operative pain and improving the quality of recovery in patients with burn wounds undergoing tangential excision skin grafting

Abstract: Burn-induced acute post-operative pain and the associated stress response may result in prolonged convalescence. The present study investigated the effects of dexmedetomidine (DEX) administration on post-operative pain and the quality of recovery following surgical treatment of moderate-to-severe burn injuries. A total of 60 adult patients undergoing tangential excision skin grafting were randomized into two groups. The DEX group (Group D) received an intravenous (i.v.) single-dose bolus injection of DEX 0.5 µ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Dexmedetomidine has gained popularity in various kinds of diseases ( Su et al, 2016 ), but its clinical use in burn treatment is still limited. Jiang et al (2019) reported that it can be successfully used for perioperative sedation in burn patients. Asmussen et al (2013) found the beneficial effects of dexmedetomidine in burn patients.…”
Section: Introductionmentioning
confidence: 99%
“…Dexmedetomidine has gained popularity in various kinds of diseases ( Su et al, 2016 ), but its clinical use in burn treatment is still limited. Jiang et al (2019) reported that it can be successfully used for perioperative sedation in burn patients. Asmussen et al (2013) found the beneficial effects of dexmedetomidine in burn patients.…”
Section: Introductionmentioning
confidence: 99%
“…There were 33 RCTs with 2676 patients included in this review, and the PRISMA flow diagram 41 is displayed in Figure 1. 42–74 All but 8 RCTs 43,49,50,52,54,64,65,74 included at least 1 secondary outcome. Seven studies 46,55,57,62,68,69,71 premedicated their patients with benzodiazepines.…”
Section: Resultsmentioning
confidence: 99%
“…PACU LOS was reported as the time to reaching a prespecified Aldrete score in 16 studies: ≥8 and 9 in 11 studies, 45,47,48,[54][55][56]60,63,68,70,72 >9 in 4 studies, [64][65][66]69 and as per institute's criteria in 1 study. 42 One study 61 relied on anesthetist judgment, and 3 studies 44,52,53 cited local criteria to determine discharge from the PACU.…”
Section: Results Of Synthesismentioning
confidence: 99%
“…Dexmedetomidine is considered a reliable treatment option for the prevention and treatment of delirium in ICU patients which could facilitate faster weaning from mechanical ventilation when compared with conventional sedation agents [6,7]. A number of publications support the advantageous profile for sedation and analgesia in intubated and mechanically ventilated burn patients during treatment in the intensive care unit and sedation prior to and/or during burns debridement and dressings or other procedures on nonintubated burn patients [8][9][10][11][12][13][14]. Dexmedetomidine has an acceptable tolerability profile; with hypotension, hypertension, and bradycardia being the most commonly reported adverse reactions [15].…”
Section: Introductionmentioning
confidence: 99%